Principal Academic Supervision in the Construction of Merdeka Curriculum Based on Humanistic Spiritual Values - Yulius Rustan Effendi; Busra Bumbungan (Jurnal Pendidikan dan Pengajaran, 2023)
The low quality of learning today is marked by the low learning outcomes of students. One of the indicators causing the low quality of learning is the need for school principals in academic supervision activities to leverage and empower the teaching potential of teachers. Thus, it is important to construct principals' academic supervision activities based on humanistic spirituality values according to the Merdeka curriculum guidelines. The purpose of this study is to describe the reasons for implementing humanistic spiritual values and the role of the principal in academic supervision activities. The research method uses qualitative research and case study design. The participants in this study were three principals and three senior teachers from the two schools studied—data collection through interviews, observation, and documentation studies. Data analysis used a modified analytic analysis method. The study results explain the reason for the principal's application of humanistic spiritual values (personal characteristics, the spirit that is lived in the school environment, and the appreciation of religious teachings) in academic supervision. In addition, the role of the principal in academic supervision is proven through ethical behavior, sincerity, patience, humility, sensibility, friendliness, equality, open communication, and mutual respect. This research has implications for the development of school principals' academic supervision based on humanistic spiritual values to empower the teaching potential of teachers, as evidenced by an increase in student achievement motivation.